Effect of flywheel resistance exercises on oxidative stress and record level of 100m backstroke for young swimmers - Bakry, O.; Elhabashy, A.; Cazan, F.; Dragomir, L.; Amr, H. (Science, Movement & Health, 2022)
Aim. Use of inertial flywheel for multi-directional movements in certain sporting conditions leads to greater improvements in performance compared to conventional training. The aim of this study was to investigate effectiveness of flywheel resistance exercises on oxidative stress and record level of 100m backstroke for young swimmers. Methods. The main sample was selected from the Benha Sports Club, (22) swimmers under 16 years old, and (4) juniors were excluded as an exploratory study, so that the actual research sample consisted of (18) swimmers, samples were divided equally into two groups, one experimental and the other control group. Experimental group practiced 10-weeks of flywheel resistance training, and the control group practiced 10-weeks of traditional swimming training. The data collected before - after the training programs for the two groups. Results. Statistical analyses showed that: Significant Difference between the experimental group and control group in all physical variables for posttest to the experimental group. Significant Difference between the experimental group and control group in (Superoxide dismutase, Catalase, Malondialdehyde) for posttest to the experimental group. Non-Significant Difference between the experimental group and control group in in 100m backstroke record Conclusions. Under the conditions of our article, the researcher conclusion that ten weeks of flywheel resistance training contributed to improving oxidative stress and record level of 100m backstroke for young swimmers.